ANALISA MANAJEMEN RESIKO DENGAN METODE FAULT THREE ANALISYS (FTA) SYSTEM COMPRESSOR AIR MINUM DALAM KEMASAN PT. SWABINA GATRA - Rizky Adi Kurniawan (LPPM Politeknik LP3I Medan, 2022)
Occupational safety and health is now starting to be important for the wider community in Indonesia, especially for employees and industrial workers, considering the growing economy and industry as well as general development, the greater the potential for harm caused. Actually this problem can be overcome by applying existing methods such as Fault Three Analysis (FTA). The purpose of this research is to carry out risk management on work equipment system failures as an effort to control work accidents at PT. Swabina Gatra The design of this research is descriptive. Hazard identification in this research uses the (HIRARC) method then the hazard result with the highest value is used as the Top Event in the Fault Three Analysis (FTA) method. The implementation stage of this method is to identify the potential and overcome hazards in the Compressor System Unit for Bottled Drinking Water PT. Swabina Gatra. The results showed that there were 7 cut-sets or causes of failure in the compressor system. The cut-set results obtained by the prevention stage which are enforced are the provision of Earth-Leakage Circuit Breakers (ELCB) on the electric panel compressor system, Perform periodic pressure vessel calibration tests no later than once every 5 years, Work in accordance with SOPs or work instructions that have been set by the Company , and conduct periodic inspections or inspections and schedule repairs and maintenance.